Recent Advances in Chinese Herbal Medicine for Cerebral Ischemic Reperfusion Injury - Huang, Ping; Wan, Haitong; Shao, Chongyu; Li, Chang; Zhang, Ling; He, Yu (Frontiers in Pharmacology, 2022)
Cerebral ischemic reperfusion injury (CI/RI) is a critical factor which leads to a poor prognosis in patients with ischemic stroke. It is an extremely complicated pathological process which clinically characterized by high rates of disability and mortality. Current available treatments for CI/RI, including mechanical therapies and drug therapies, are often accompanied by significant side-effects. Therefore, it is necessary to discovery new strategy for treating CI/RI. Many studies have confirmed that the Chinese herbal medicine (CHM) was used as potential drug for treatment of CI/RI with the advantages of abundant resources, good efficacy and little side effects. In this paper, we investigate the latest drug discoveries and advancements on CI/RI, make an overview of relevant CHM, systematically summarize the pathophysiology of CI/RI. In addition, the protective effect and mechanism of related CHM, which includes extraction of single CHM, CHM formulation and preparation, are discussed. Moreover, an outline of the limitations of CHM and the challenges we faced are also presented. This review will be helpful for the researchers further propelling the advancement of drugs and supplying more knowledge to support the application of previous discoveries in clinical drug applications against CI/RI.